Pengaruh Penerimaan Teknologi Melalui Behavioral Intention Sebagai Variabel Moderasi Terhadap Actual Usage Zenius Education - Aulia Rahmah; Rd. Funny Mustikasari Elita; Slamet Mulyana (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
This research aims to determine how significant the influence of technology acceptance through behavioral intention as a moderating variable is on actual usage of Zenius Education using the Technology Acceptance Model. Apart from that, this research looks at the influence of behavioral intention as a moderating variable. This research used a quantitative method by distributing questionnaires to 67 research samples online in the form of a Google Form. Hypothesis testing in this research uses path analysis and coefficient of determination. The results of this research show that perceived usefulness (X1) and perceived ease of use (X2) have a significant effect on the actual use of Zenius Education. Furthermore, behavioral intention as a moderating variable has a significant influence in mediating technology acceptance on actual use.